Contraceptive stockouts in Western Kenya: a mixed-methods mystery client study - Tumlinson, Katherine; Britton, Laura E.; Goland, Emilia; Chung, Stephanie; Bullington, Brooke W.; Williams, Caitlin R.; Wambua, Debborah Muthoki; Onyango, Dickens Otieno; Senderowicz, Leigh (BioMed Central Ltd., 2023)
Background: The prevalence of modern contraception use is higher in Kenya than in most countries in Sub-Saharan Africa. The uptake has however slowed down in recent years, which, among other factors, has been attributed to challenges in the supply chain and increasing stockouts of family planning commodities. Research on the frequency of contraceptive stockouts and its consequences for women in Kenya is still limited and mainly based on facility audits. Methods: This study employs a set of methods that includes mystery clients, focus group discussions, key informant interviews, and journey mapping workshops. Using this multi-method approach, we aim to quantify the frequency of method denial resulting from contraceptive stockout and describe the impact of stockouts on the lived experiences of women seeking contraception in Western Kenya. Results: Contraceptives were found to be out of stock in 19% of visits made to health facilities by mystery clients, with all contraceptive methods stocked out in 9% of visits. Women experienced stockouts as a sizeable barrier to accessing their preferred method of contraception and a reason for taking up non-preferred methods, which has dire consequences for heath, autonomy, and the ability to prevent unintended pregnancy. Reasons for contraceptive stockouts are many and complex, and often linked to challenges in the supply chain – including inefficient planning, procurement, and distribution of family planning commodities. Conclusions: Contraceptive stockouts are frequent and negatively impact patients, providers, and communities. Based on the findings of this study, the authors identify areas where funding and sustained action have the potential to ameliorate the frequency and severity of contraceptive stockouts, including more regular deliveries, in-person data collection, and use of data for forecasting, and point to areas where further research is needed.
Keywords: Contraceptive stockouts; Contraceptive supply; Family planning; Health services; Reproductive health; Health Policy